2016
DOI: 10.1080/10401334.2016.1230501
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Learning Goals: Using Self-Regulated Learning to Influence Day-to-Day Practice in Clinical Education

Abstract: Student-generated weekly learning goals on a neurology clerkship appear to be an effective method to operationalize SRL. For most students, the frequency of the goals allowed for close self-monitoring, and the act of sharing goals with the team opened a new avenue for dialogue between students and their supervisors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…In consequence, students felt they were then forced to continuously adjust and refine their goals based on observation of and negotiation with residents, physicians and peers, as well as on actual learning and work experiences. These findings are in line with those of previous studies which showed that goal setting in clinical contexts requires negotiation between students and supervisors and engagement from supervisors if goals are to be realistic and attainable …”
Section: Discussionsupporting
confidence: 92%
“…In consequence, students felt they were then forced to continuously adjust and refine their goals based on observation of and negotiation with residents, physicians and peers, as well as on actual learning and work experiences. These findings are in line with those of previous studies which showed that goal setting in clinical contexts requires negotiation between students and supervisors and engagement from supervisors if goals are to be realistic and attainable …”
Section: Discussionsupporting
confidence: 92%
“…in their study of medical student clinical learning. Indeed, several investigations have found collaborative dialogue to be essential for successful implementation of ostensibly SRL educational interventions whether they be clerkship student learning goals or resident individualised learning plans . Berkhout et al .…”
mentioning
confidence: 99%
“…Indeed, several investigations have found collaborative dialogue to be essential for successful implementation of ostensibly SRL educational interventions whether they be clerkship student learning goals or resident individualised learning plans. [16][17][18] Berkhout et al 19 showed that as learners became more experienced in workplace learning, their pursuit of SRL became increasingly collaborative with supervisors. In another study of student learning in a surgical environment, students with the broadest learning experiences leveraged their interactions with supervisors to create desired educational opportunities.…”
Section: Douglas P Larsenmentioning
confidence: 99%